Pharmacy diabetes screening trial (PDST): Outcomes of a national clustered RCT comparing three screening methods for undiagnosed type 2 diabetes (T2DM) in community pharmacy. (March 2023) - Krass, Ines; Carter, Rob; Mitchell, Bernadette; Mohebbi, Mohammadreza; Shih, Sophy T.F.; Trinder, Peta; Versace, Vincent L.; Wilson, Frances; Mc Namara, Kevin P.
Abstract: Aims: To compare the effectiveness of three pharmacy-based screening methods for type 2 diabetes (T2DM): (1) risk assessment (AUSDRISK) alone (Group A); AUSDRISK followed by a point of care test if AUSDRISK ≥12; either (2) HbA1c (Group B); or (3) small capillary blood glucose test (Group C). Methods: A cluster RCT with a nationally representative sample of Australian pharmacies was implemented with random allocation of eligible pharmacies to Groups A, B or C. GP referral was based on prespecified cut offs. Diagnoses were considered positive if confirmed by a GP, pathology laboratory, or national diabetes register. Results: Of the 14, 093 people screened in 339 pharmacies, 3059 participants met group-specific referral criteria: 1775 (45%) (Group A); 893 (17%) (Group B); and 391 (8%) (Group C). For the total screened population rates of T2DM diagnoses were significantly higher in Group B (1.5%), compared with Groups A (< 0.8%) and C (< 0.6%) with the odds of detection in Group B compared with Group A (1.8 [1.0;3.0]), and no difference between Groups A and C. Conclusions: In community pharmacy, the most effective method to uncover undiagnosed T2DM was a stepwise approach; initial risk assessment; and if appropriate an HbA1C POC test and referral.